Using Focus Groups to Develop an Extension Home Horticulture Public Radio Program - Courtney Meyers; Tracy Irani; Erin Eckhardt (Journal of Applied Communications, 2006)
Since its creation in 1914, Cooperative Extension has evolved to include a variety of traditional and nontraditional program areas. To reach new clientele, Extension must create programs that appeal to more generalized audiences and that communicate public value. One area that has the potential to create public value with nonagriculturalists is home horticulture. The application of marketing analysis, planning, implementation, and management should be used to reach this audience and provide better service. The University of Florida Extension Service uses an integrated marketing communication (IMC) approach to convey the role Extension plays in the state and in local communities. One component of this approach has been the development of a home horticulture radio show to be broadcast on National Public Radio (NPR) stations. Two focus groups consisting of target audience members (both users and nonusers of Extension) evaluated potential topics and formats for the radio program. Participants preferred topics dealing with plant selection and basic maintenance in the climatic zone of North Central Florida. They preferred the radio show name to mention the 2-minute time format and favored the use of the word "gardening" over "landscaping." They also wanted the radio show to be linked to a Web site and wanted both the Web site and radio show to use a question-and-answer format. Overall, the focus group method was effective in discovering audience preferences.